Prefabricated wood i-joist from Keruing (Dipterocarpus spp.) flanges and plywood (Hevea brasiliensis) web / Mohd Azri Azmy - Azmy, Mohd Azri (2001)
Wood l-joist is a system that consist of flange and web component. Both components have work together as a system in order to match the strength property of a solid wood beam. The objective of the study is to obtain strength properties of prefabricated wood I-joist made from L-butt jointed web (Plywood: Hevea brasiliensis) and Dipterocarpus spp. flanges which used PRF (Phenol Resorcinol Formaldehyde) adhesive as a joint binder. The I-joist was combine with synthetic materials, resulting in lightweight, strong and environment-friendly building materials. The average of modulus of rupture (MOR) for the study was 15.4 MPa and the average value of modulus of elasticity (MOE) was 15,961 MPa. As the conclusion to this study, plywood web and solid wood flanges as an I-joist system cannot perform as a system.